Modeling systems from partial observations - Champaney, Victor; Amores, Víctor J.; Garois, Sevan; Irastorza-Valera, Luis; Ghnatios, Chady; Montáns, Francisco J.; Cueto, Elías; Chinesta, Francisco (Frontiers in Materials, 2022)
Modeling systems from collected data faces two main difficulties: the first one concerns the choice of measurable variables that will define the learnt model features, which should be the ones concerned by the addressed physics, optimally neither more nor less than the essential ones. The second one is linked to accessibility to data since, generally, only limited parts of the system are accessible to perform measurements. This work revisits some aspects related to the observation, description, and modeling of systems that are only partially accessible and shows that a model can be defined when the loading in unresolved degrees of freedom remains unaltered in the different experiments.